The chemical compositions of accreted and in situ galactic globular clusters according to SDSS/APOGEE. Issue 3 (18th February 2020) - Horta, Danny; Schiavon, Ricardo P; Mackereth, J Ted; Beers, Timothy C; Fernández-Trincado, José G; Frinchaboy, Peter M; García-Hernández, D A; Geisler, Doug; Hasselquist, Sten; Jönsson, Henrik; Lane, Richard R; Majewski, Steven R; et al.
ABSTRACT: Studies of the kinematics and chemical compositions of Galactic globular clusters (GCs) enable the reconstruction of the history of star formation, chemical evolution, and mass assembly of the Galaxy. Using the latest data release (DR16) of the SDSS/APOGEE survey, we identify 3090 stars associated with 46 GCs. Using a previously defined kinematic association, we break the sample down into eight separate groups and examine how the kinematics-based classification maps into chemical composition space, considering only α (mostly Si and Mg) elements and Fe. Our results show that (i) the loci of both in situ and accreted subgroups in chemical space match those of their field counterparts; (ii) GCs from different individual accreted subgroups occupy the same locus in chemical space. This could either mean that they share a similar origin or that they are associated with distinct satellites which underwent similar chemical enrichment histories; (iii) the chemical compositions of the GCs associated with the low orbital energy subgroup defined by Massari and collaborators is broadly consistent with an in situ origin. However, at the low-metallicity end, the distinction between accreted and in situ populations is blurred; (iv) regarding the status of GCs whose origin is ambiguous, we conclude the following: the position in Si–Fe plane suggests an in situ origin for Liller 1 and a likely accreted origin for NGC 5904 and NGC 6388. The case of NGC 288 is unclear, as its orbital properties suggest an accretion origin, its chemical composition suggests it may have formed in situ .